STUDY ON THE PHYSICOCHEMICAL, ANTIOXIDANT PROPERTIES AND MINERAL CONTENT OF FIVE HONEYS PRODUCED IN THE CENTRAL REGION OF ALGERIA - MOUNIR HABATI; ABDELAZIZ GHERIB; BOULANOUAR BAKCHICHE; AHMED. A. BENMEBAREK (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2017)
The present study evaluated the physicochemical, antioxidant properties and mineral content of five Honeys from the Central Region of Algeria (Laghouat). Physicochemical properties were examined according to the official methods of analysis of AOAC (Association of Official Analytical Chemists); antioxidant activities were determined by DPPH (2,2-diphenyl-1-picrylhydrazyl) and FRAP (Ferric reducing ability of plasma) assays, the minerals were analyzed by atomic absorption spectrometry. The results compared to those recommended by Codex Alimentarius indicated that the quality of the tested honey was very good. The samples exhibited good antioxidant activity. A linear positive relationship existed between antioxidant activity and total phenolics (R2 = 0.95)/flavonoids (R2 = 0.99). The analyzed honey samples possess valuable antioxidants for culinary and medicinal uses. The analysis revealed the presence of (K) 220.88 ± 1.72 ppm, (Na) 85.84 ± 1.72 ppm, (Fe) 0.1922 ± 0.47 ppm, (Co) 0.9144 ± 1.63 ppm, (Cu) 0.1252 ± 1.76 ppm and nickel (Ni) 0.0463 ± 0.10 ppm in the collected samples. Toxic elements identified in the studied honeys are safe because they are below the maximum residual limit. Therefore, these results indicate that the areas of production of these honeys are unpolluted by the toxic elements.